High efficiency, 41.6 W, 10 kHz picosecond output based on a Nd:YAG double-pass multi-folded Innoslab amplifier. (April 2022) - Ma, Chao; Liu, Zhao; Liu, Ke; Yu, Yang; Wang, Xiao-jun; Bo, Yong; Cui, Da-fu; Peng, Qin-jun
Abstract: We designed a novel structure of double-pass multi-folded partially-end-pumped slab (Innoslab) amplifier, which could effectively improve the extraction efficiency. High efficiency and high power picosecond (ps) radiation was obtained by the Nd:YAG Innoslab amplifier. A 4.5 W seed at a repetition rate of 10 kHz was amplified to 41.6 W under an absorbed pump power of 124.7 W, corresponding to extraction efficiency of 29.8%. The pulse duration was approximately 86.5 ps, and the corresponding peak power was up to 48.1 MW. The beam quality factor M 2 at the maximum output power was measured to be 2.28 and 1.52 in the horizontal and vertical directions, respectively. To the best of our knowledge, this study was the first to report high efficiency double-pass multi-folded Innoslab amplifier.